1983
DOI: 10.1093/oxfordjournals.jbchem.a134316
|View full text |Cite
|
Sign up to set email alerts
|

Differential Reactivities of Fucosyl GM1 and GM1 Gangliosides on Rat Erythrocyte Membrane Revealed by Analysis with Anti-Fucosyl GM1 and GM1 Antisera1

Abstract: Rat erythrocytes contained ganglio-series gangliosides, GM1, fucosyl GM1, and GD1a, in a high concentration. The concentrations of GM1, fucosyl GM1, and GD1a in rat erythrocyte ghosts were 889.0 nmol, 470.6 nmol, and 462.0 nmol per g dry weight, respectively, and the molar ratio of lipid-bound sialic acid, cholesterol and lipid-bound phosphorus was 3.1:73.9:100.0. The reactions of fucosyl GM1 and GM1 on rat erythrocytes with rabbit anti-fucosyl GM1 and anti-GM1 antisera were measured by means of haemolysis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…4, lane 2) as well as the control IV6NeuAc-nLc4Cer from human meconium (Fig. 4, lane 1) (21). Differences in mobility on TLC plates may be due to the structural difference in their ceramide moieties.…”
Section: Resultsmentioning
confidence: 91%
“…4, lane 2) as well as the control IV6NeuAc-nLc4Cer from human meconium (Fig. 4, lane 1) (21). Differences in mobility on TLC plates may be due to the structural difference in their ceramide moieties.…”
Section: Resultsmentioning
confidence: 91%
“…As to GM1 on RRBC, we previously found that its reactivity was confined to small ligands on flow cytometric analysis, that is, cholera toxin B-subunit (56 kDa in molecular weight) had the ability to bind with GM1 readily bound to RRBC, but anti-GM1 antibodies (150 to 970 kDa in molecular weight) could not bind to RRBC at all [16,27]. Thus, one of the reasons why anti-GM1 antibodies were not produced on immunization with RRBC was supposed to be the masking of GM1 by coexisting molecules on RRBC, and the conformation of GM1 probably differs from those of Gg 4 Cer, the unknown glycolipid (IV 2 Fucα, IV 3 Galα-Gg 4 Cer), and FGM1, all of which effectively produced antibodies to themselves in anti-RRBC antisera.…”
Section: Discussionmentioning
confidence: 99%
“…), and fractionated into neutral and acidic lipids on a DEAE-Sephadex column (A-25, acetate form; GE Healthcare). Then, the neutral glycolipids were separated from the unabsorbed neutral lipid fraction by acetylation, separation of the acetylated derivatives, deacetylation and desalting, whereas the gangliosides were prepared from the absorbed acidic lipid fraction by cleavage of the ester-containing lipids, followed by dialysis [16,17]. The gangliosides and neutral glycolipids thus obtained were examined by TLC as above.…”
Section: Separation and Quantitation Of Glycolipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of total lipids from human meconium (A and O donors), followed by fractionation into neutral and acidic lipids by DEAE-Sephadex (A-25, acetate form) column chromatography, was carried out as described previously [1,2]. The acidic glycosphingolipids were prepared from the acidic fraction by saponification and dialysis, and then purified by ganglioside-mapping [3] and high-performance liquid chromatography (HPLC) on a column (2 cm internal diameter x 25 cm) packed with Iatrobeads (6RS8010).…”
Section: Glycosphingolipids From Human Meconiummentioning
confidence: 99%